Mimicry and Multiculturalism from Colonial and Postcolonial Perspective in Rudyard Kipling’s ''Kim'' and Arundhati Roy’s ''The God of Small Thing'' - Assist Lect. Rakan Assi Khalaf Assist Lect. Rakan Assi Khalaf (مجلة النور للدراسات الانسانية)
ABSTRACT